Highly active and stable Ni–W/SiO2 catalyst derived from W incorporated on Ni phyllosilicate for deoxygenation of triglycerides into green biofuel range hydrocarbons - Wanichaya Praikaew; Jedy Prameswari; Sakhon Ratchahat; Weerawut Chaiwat; Chularat Sakdaronnarong; Wanida Koo-amornpattana; Wanwisa Limphirat; Suttichai Assabumrungrat; Yu‐Chuan Lin; Kittisak Choojun; Tawan Sooknoi; Atthapon Srifa (Energy Conversion and Management X, 2025)
• Highly active and stable W–Ni/SiO 2 catalyst synthesized via ammonia evaporation. • W incorporation enhanced H 2 activation and increased Lewis acidity. • Ni–WO x –acid sites synergy enabled selective hydrocarbon production from triglycerides. • In situ/ex situ confirmed well-dispersed Ni with small size and catalyst structure. • 5 W/Ni-AE achieved 70 % yield of jet and diesel fuels with excellent 60 h stability. Highly active and stable Ni–W/SiO 2 catalyst derived from W incorporated into Ni phyllosilicate (Ni-PS) was prepared by the ammonia evaporation (AE) method, and benchmarked with the catalyst prepared by the impregnation method (IM). Their catalytic activities were evaluated for deoxygenation of triglycerides into green biofuel-range hydrocarbons. The Ni-PS structure demonstrated a large surface area with strong interaction between Ni 2+ and SiO 2 , resulting from the incorporation of Ni 2+ into the silica framework, which led to highly dispersed Ni⁰ after H 2 reduction. Additionally, the H 2 adsorption and desorption capabilities, together with a substantial quantity of Lewis acid sites, were advantageous features of Ni-PS catalysts compared to Ni-IM and 5 W/Ni-IM catalysts. Ex situ and in situ structural characterizations revealed the generation of Ni⁰ and W⁰ states, along with remaining W 4+ species after H 2 reduction. The 5 W/Ni-AE catalyst exhibited stable performance up to 60 h on stream, producing consistent yields of 30 % jet fuel and 40 % diesel, which was attributed to its high porosity, small Ni⁰ particle sizes, enhanced H 2 adsorption–desorption capacities, and abundant Lewis acid sites. Consequently, the heterogeneous 5 W/Ni-AE catalyst shows significant practical relevance for generating green biofuel from oil-derived feedstock in sustainable biorefineries.
Keywords: Catalysis and Hydrodesulfurization Studies; Catalysis for Biomass Conversion; Catalytic Processes in Materials Science